2018
DOI: 10.1111/cas.13807
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A1 polymorphisms in rectal cancer associated with the efficacy and toxicity of preoperative chemoradiotherapy using irinotecan

Abstract: The purpose of the present study was to assess the efficacy and toxicity of preoperative chemoradiotherapy using irinotecan against locally advanced lower rectal cancer according to UDP‐glucuronosyltransferase 1A1 (UGT1A1) polymorphisms. Between 2009 and 2016, 46 patients with resectable rectal cancer (T3‐T4, N0‐N2, M0) received preoperative chemoradiotherapy consisting of 80 mg/m2 per day tegafur/gimeracil/oteracil (S‐1; days 1‐5, 8‐12, 22‐26, and 29‐33), 60 mg/m2 per day irinotecan (days 1, 8, 22, and 29), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Except for monotherapy, preclinical studies have demonstrated the synergistic antiproliferative and pro-apoptotic activity of irinotecan or topotecan and aaTKIs in vitro, and the improvement of the in vivo anticancer activity on angiogenesis, endothelial and cancer cells, such as pancreatic (40) and ovarian cancer cells (41). Based on the non-overlapped adverse effects of irinotecan (42,43) and aaTKIs (44,45), these studies suggested a possible translation of this combination into the clinic. A phase I study of axitinib and irinotecan combined with 5-fluorouracil and leucovorin in patients with advanced colorectal cancer described an acceptable toxicity profile (46).…”
Section: Discussionmentioning
confidence: 99%
“…Except for monotherapy, preclinical studies have demonstrated the synergistic antiproliferative and pro-apoptotic activity of irinotecan or topotecan and aaTKIs in vitro, and the improvement of the in vivo anticancer activity on angiogenesis, endothelial and cancer cells, such as pancreatic (40) and ovarian cancer cells (41). Based on the non-overlapped adverse effects of irinotecan (42,43) and aaTKIs (44,45), these studies suggested a possible translation of this combination into the clinic. A phase I study of axitinib and irinotecan combined with 5-fluorouracil and leucovorin in patients with advanced colorectal cancer described an acceptable toxicity profile (46).…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are a limited amount of reports about UGT1A1 genotype and CPT-11 participating in nCRT of LARC patients. We only retrieved two studies in this field on the United States National Library of Medicine National Institutes of Health website, among which Kimura results [49] showed that the polymorphism of UGT1A1 affected the incidence of neutropenia. The level 3-4 neutropenia and leucopenia in heterozygote and homozygote groups were significantly higher than those in the wild-type group, but the effect on diarrhea was not found.…”
Section: Irinotecanmentioning
confidence: 99%
“…Following exclusion criteria, 195 articles were removed, and the rest 106 full-texts articles were assessed in depth following eligibility criteria. Finally, 42 articles were included in this meta-analysis for assessing the associations ofUGT1A1*6/*28 or ABCC2 c.3972C>T with irinotecan induced severe toxicities [12,14,21,[22][23][24][26][27][28][29][30][31]34,35,]. The complete selection process of articles following PRISMA guidelines is shown in Figure 1.…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
“…When patients inheriting both of these polymorphisms (UGT1A1*6 and UGT1A1*28), the toxicities of irinotecan may be exacerbated profoundly due to combined genetic effects as evidenced in some studies [14,[26][27][28] although the results are again inconclusive and inconsistent as found in other studies [18,[29][30][31]. In these controversial clinical situations, it is also important to noted that in addition to the UGT1A1 enzyme, irinotecan, SN-38 and SN-38G are transported out of the cell into bile by members of the ATP-binding cassette (ABC) transporter family especially ABCC2 encoded by theABCC2 gene [32,33].…”
Section: Introductionmentioning
confidence: 97%